A clinician’s perspective on the new organ mesentery and non-vascular mesenteropathies - Ahmed, Monjur (Frontiers in Physiology, 2024)
Mesentery was discovered as a new organ in 2017. It is a continuous membranous tissue from the duodenojejunal flexure to the anorectal junction. It has distinct anatomy, physiology, and disease states. Primary mesenteropathies include vascular and non-vascular diseases. Some of them are common, and some of them are rarely seen in clinical practice. Secondary mesenteropathies occur when infection or malignancy in another organ spreads to the mesentery. Each entity has specific diagnostic and treatment protocols. Increased awareness of different mesenteropathies and an understanding of their various presentations at different stages of life can help in early diagnosis and improved clinical outcomes.